Identification and validation of a small molecule targeting ROR1 for the treatment of triple negative breast cancer - Gupta, Shradheya R. R.; Ta, Tram M.; Khan, Maryam; Singh, Archana; Singh, Indrakant K.; Peethambaran, Bela (Frontiers in Cell and Developmental Biology, 2023)
Breast cancer is the most common cancer in women, with roughly 10-15% of new cases classified as triple-negative breast cancer (TNBC). Traditional chemotherapies are often toxic to normal cells. Therefore, it is important to discover new anticancer compounds that target TNBC while causing minimal damage to normal cells. Receptor tyrosine kinase-like Orphan Receptor 1 (ROR1) is an oncofetal protein overexpressed in numerous human malignancies, including TNBC. This study investigated potential small molecules targeting ROR1. Compound 4 (CID1261330) had docking scores of -6.635 and -10.8. It fits into the pocket and shows interactions with GLU64, ASP174, and PHE93. Its RMSD fluctuates around 0.20 nm and forms two stable H-bonds indicating compound 4 stability. It inhibits cell proliferation in MDA-MB-231, HCC1937 and HCC1395 cell lines, with IC50 values of approximately 2 μM to 10 μM, respectively. Compound 4 did not kill non-malignant epithelial breast cells MCF-10A (IC50 > 27 μM). These results were confirmed by the significant number of apoptotic cells in MDA-MB-231 cells (47.6%) but not in MCF-10A cells (7.3%). Immunoblot analysis provided additional support in the same direction. These findings collectively suggest that compound 4 has the potential to effectively eliminate TNBC cells while causing minimal harm to normal breast cells. The promising outcomes of this study lay the groundwork for further testing of compound 4 in other malignancies characterized by ROR1 upregulation, serving as a proof-of-concept for its broader applicability.